URBANIZATION AND DEMOGRAPHIC FACTORS AS INDICES OF HEALTH BEHAVIOUR OF RURAL AND URBAN COMMUNITIES IN OYO STATE, NIGERIA (1985)
The focus of this thesis was to find out the influence of urbanisation and demographic factors on the health behaviour of the rural and urban communities in Oyo State, Nigeria. A knowledge of the local situation on the influence of urbanisation and demographic factors was lacking. The study provided a vital link between foreign researches in this direction and the local situation. Besides, the study provided an insight into the health behaviour pattern of rural and urban dwellers. Thus health planners would be aided in designing programmes to tackle specific health problems in varying cultures from the information in this study. The study was limited to three urban towns in different stages of industrial and population growth. They were Eruwa (pre-industrial town), Osogbo (industrial or urban City) and Ibadan (metropolitan). Two sets of rural settlements were also used for this study. They were the remote rural communities which include Ogboro, Tewure and Imini. The second group was the urban fringed rural settlements which also inelude Oko, Kuta and Erimo. The health behaviour characteristics investigated were avenues sought for treatment during illness, drug use, and nutrition. The demographic factors that were examined as to their influence on the respondents in this study were education, inoome, age, sex and marital status. 983 subjects were selected for this study. The method of selection was based on different proportional representation of each study area in relation to their population. The main research tool in this study was questionnaire. It was designed by the researcher with the assistance of the project supervisor. Pilot testing of the questionnaire was carried out to correct ambiguity in the questionnaire and to improve on the qualities of measurement and discriminability of the questionnaire. The sampling technique employed in the distribution of the questionnaire was clustered sampling. The main statistical tool used in the analysis was chisquare and percentages. The conclusions from the study were that urbanisation and demographic factors influenced the health behaviour of the respondents in respect of avenues.